If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying n + -57 = 19 Reorder the terms: -57 + n = 19 Solving -57 + n = 19 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '57' to each side of the equation. -57 + 57 + n = 19 + 57 Combine like terms: -57 + 57 = 0 0 + n = 19 + 57 n = 19 + 57 Combine like terms: 19 + 57 = 76 n = 76 Simplifying n = 76
| h-49=0 | | 4+3n=5(2-2n) | | 16=s-50 | | 29=q-51 | | 3a+5b=15 | | 8k+5k-10k= | | 56-d=27 | | 2+2u+7=42 | | w-10=58 | | 6=k-15 | | 4=m-63 | | 7x-3=x+7 | | 12-(3x-6)-5(7-x)= | | 39-w=2 | | y-65=9 | | (4t+9)-(-2+7)=0 | | A=p+pnr | | p-10=25 | | 8=n-65 | | 52q=32 | | b^4-ab^3+b^2c=0 | | 7*cos^2*x-cos*x-8=0 | | 71=-9n+8 | | 3*cos*2*x-5*cos*x-1=0 | | -3(y-2)=-5y+18 | | 7w-9=5(w+1) | | 7(y+6)-2y=2 | | 22-2x=14 | | .5x-2.4=.6 | | -4v+8(v-2)=-4 | | -3(4t-3)+5t=6t-5 | | 48+x(9+3)=288 |